2020
DOI: 10.3390/plants9111483
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Characterization of Δ12-Fatty Acid Acetylenase and Δ12-Oleate Desaturase Potentially Involved in the Polyacetylene Biosynthetic Pathway from Bidens pilosa

Abstract: Bidens pilosa is commonly used as an herbal tea component or traditional medicine for treating several diseases, including diabetes. Polyacetylenes have two or more carbon–carbon triple bonds or alkynyl functional groups and are mainly derived from fatty acid and polyketide precursors. Here, we report the cloning of full-length cDNAs that encode 12-fatty acid acetylenase (designated BPFAA) and 12-oleate desaturase (designated BPOD) from B. pilosa, which we predicted to play a role in the polyacetylene biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…ntioxidants 2021, 10, x FOR PEER REVIEW 10 of 13 was observed in the ex-vitro-grown KP-BG leaves (Table 2). In plants, ∆ 12 -fatty acid desaturase catalyzes the conversion of C18:1n9c (OA) to C18:2n6c (LA) [61]. Comparison of OA:LA peaks can be discussed, as the OA:LA ratio is 0.17 in in-vitro-raised KP-BG leaves and 1.5 in leaves obtained from ex-vitro-grown KP-BG plants (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…ntioxidants 2021, 10, x FOR PEER REVIEW 10 of 13 was observed in the ex-vitro-grown KP-BG leaves (Table 2). In plants, ∆ 12 -fatty acid desaturase catalyzes the conversion of C18:1n9c (OA) to C18:2n6c (LA) [61]. Comparison of OA:LA peaks can be discussed, as the OA:LA ratio is 0.17 in in-vitro-raised KP-BG leaves and 1.5 in leaves obtained from ex-vitro-grown KP-BG plants (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three pathways into polyacetylene space, the crepenynate pathway has been studied the most. Several groups, working with various Asterales or Apiales species, have identified FAD2 family genes that encode enzymes with oleic acid Δ12 acetylenase (i.e., a triple bond‐forming desaturase) activity and thus have the ability to produce crepenynic acid (Figure 3b) (Cahoon et al., 2003; Chen et al., 2020; Lee et al., 1998; Nam & Kappock, 2007). Further work revealed that certain FAD2 genes encode enzymes with crepenynic acid Δ14 desaturase activity, yielding dehydrocrepenynic acid (DCAR_013547; Figure 3b) (Busta et al., 2018).…”
Section: Main Textmentioning
confidence: 99%